2006
DOI: 10.1080/15572536.2006.11832636
|View full text |Cite
|
Sign up to set email alerts
|

New insights into classification and evolution of the Lecanoromycetes (Pezizomycotina, Ascomycota) from phylogenetic analyses of three ribosomal RNA- and two protein-coding genes

Abstract: The Lecanoromycetes includes most of the lichen-forming fungal species (> 13500) and is therefore one of the most diverse class of all Fungi in terms of phenotypic complexity. We report phylogenetic relationships within the Lecanoromycetes resulting from Bayesian and maximum likelihood analyses with complementary posterior probabilities and bootstrap support values based on three combined multilocus datasets using a supermatrix approach. Nine of 10 orders and 43 of 64 families currently recognized in Eriksson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 54 publications
11
96
4
Order By: Relevance
“…Rivas Plata et al, unpublished manuscript ). This hypothesis is consistent with the fi nding that in several cases, saxicolous lichens or even nonlichenized rock fungi are basal or sister to the main lichenized lineages ( Miadlikowska et al, 2006 ;Hofstetter et al, 2007 ;Gueidan et al, 2008 ;Schoch et al, 2009 ). In many lichenized lineages, however, the immediate sister group is not known, which makes assumptions about their early evolution speculative.…”
Section: Methodssupporting
confidence: 70%
“…Rivas Plata et al, unpublished manuscript ). This hypothesis is consistent with the fi nding that in several cases, saxicolous lichens or even nonlichenized rock fungi are basal or sister to the main lichenized lineages ( Miadlikowska et al, 2006 ;Hofstetter et al, 2007 ;Gueidan et al, 2008 ;Schoch et al, 2009 ). In many lichenized lineages, however, the immediate sister group is not known, which makes assumptions about their early evolution speculative.…”
Section: Methodssupporting
confidence: 70%
“…Members of the Cladoniaceae were selected as outgroup for the analysis because previous studies suggested that these families are closely related to Parmeliaceae (Miadlikowska et al 2006;Crespo et al 2007). Details of the studied material, including GenBank accession numbers are shown in Table 1.…”
Section: Samplingmentioning
confidence: 99%
“…In the lichenforming Ascomycetes associating with cyanobacteria (cyanolichens), several recent major taxonomic changes have been proposed Wedin et al 2009;Otálora et al 2010;Muggia et al 2011;Spribille & Muggia 2012). Molecular phylogenies suggest that cyanolichens form three distinct and distantly related lineages: Arctomiaceae Wedin et al 2005) and the Peltigerales (Wedin et al 2005;Miądlikowska et al 2006) in the Lecanoromycetes, and Lichinales in the Lichinomycetes (Reeb et al 2004).…”
Section: Introductionmentioning
confidence: 99%